IMPLEMENTASI MASSAGE OLAHRAGA UNTUK PEMULIHAN SESUDAH LATIHAN BAGI ATLET FUTSAL SMAS REGINA PACIS BAJAWA - Fransiskus Leonard Bela; Yulius Marianus Jawa; Josep Marsianus Rewo (SMA Negeri 1 Bangkinang Kota, 2026)
ABSTRACT This study aims to describe the implementation of sports massage as a post-training recovery method for futsal athletes at SMAS Regina Pacis Bajawa. The study employed a qualitative method with a descriptive approach, involving 15 futsal athletes from grades X and XI and their coach as research subjects. Data were collected through observation, in-depth interviews, and documentation. The results indicate that sports massage is applied after training and matches, focusing on the thighs, calves, waist, and back muscles using effleurage, petrissage, friction, vibration, tapotement, and walken techniques for 10–20 minutes per athlete. Athletes responded positively, reporting increased relaxation, reduced muscle soreness, and improved readiness for subsequent training sessions.